Effect of TiO2 content in slag on Ti content in molten steel - Gao Gang (De Gruyter, 2021)
A calculation model of activity for CaO–SiO2–MgO–Al2O3–TiO2 slag is established according to molecular-ion coexistence theory of slag structure to calculate the activities of Al2O3, SiO2, and TiO2 in the slag. The possibility of TiO2 reduction in the slag during refining is analyzed by thermodynamics and verified by laboratory and industrial experiments. Both theoretical analysis and laboratory experimental results show that the content of TiO2 in the ladle slag significantly influences the Ti content in molten steel. When the content of the dissolved aluminum in molten steel is 0.030–0.050%, the TiO2 content in the ladle slag should be controlled below 0.3% to prevent TiO2 reduction. The critical content of TiO2 decreases with an increasing amount of the dissolved aluminum in molten steel. In addition, silicon should be used as a deoxidizer during diffused deoxidization because aluminum as a deoxidizer would lead to the reduction of TiO2. The industrial experiments confirm the results of the laboratory experiments and thermodynamics analysis.